Corneal transplantation in aniridia‐related keratopathy with a two‐year follow‐up period, an uncommon disease with precarious course. Issue 2 (9th August 2022) - Viberg, Andreas; Vicente, André; Samolov, Branka; Hjortdal, Jesper; Byström, Berit
Abstract: Purpose: The purpose of this study is to study the frequency, surgical transplantation technique and outcome in patients with aniridia‐related keratopathy (ARK) with two‐year follow‐up period. Methods: A retrospective registry‐study including all ARK cases performed in Sweden and Denmark between 2001 and 2016 and registered in the Swedish Cornea Transplant Registry. Results: A total of 36 eyes of 26 patients were subjected to corneal transplantation due to ARK during 2001 to 2016. Penetrating keratoplasty (PK) was the procedure of choice in 58.3% ( n = 21) of the eyes, followed by a combination of PK and limbal stem cell transplantation in 13.9% ( n = 5) and keratolimbal allograft in 13.9% ( n = 5). Boston keratoprosthesis was used in 8.3% ( n = 3), and anterior lamellar keratoplasty in 5.6% ( n = 2). Thirteen of the procedures (36.1%) were retransplantations. Two years after surgery 26 cases were available to follow‐up of which 16 of the grafts were functioning (61.5%). The median visual acuity showed a trend of improvement from hand motion to counting fingers. Conclusions: A majority of the ARK cases (61.5%) had a graft providing useful vision for the patient 2 years after corneal transplantation, but the visual gain was modest at best. Longer follow‐up time is required to evaluate functional graft outcomes. Despite the introduction of limbal stem cell transplantation as a suitable treatment, PK was the most common surgical method in the present study.